Effective Social Interaction Strategies for Inclusive Settings. - Terpstra, Judith; Tamura, Ronald (Early Childhood Education Journal, 2008)
Many strategies and interventions exist in the education of young children with disabilities. One area of intervention is that of social interaction, including social skills instruction, peer interaction strategies, and play skills. Interaction and social skill strategies for use with children with and without disabilities for the purpose of increasing social interactions between children with and without disabilities in educational settings is an area many educators of early childhood special education strive to find in an effective and easy to implement format. Several strategies from research are presented in this article. Only strategies that were demonstrated to be successful through reported research are discussed. Strategies are identified according to their ease of implementation and effectiveness., (C)2008 Kluwer Academic Publishers
Keywords: Peer interaction; Play skills; Play strategies; Social interaction; Social skills; Social strategies; dept.sed

Teacher and parent perspectives on extracurricular activities for students with intellectual and developmental disabilities - Cain, Irina; Bruno, Lauren; Agran, M.; Wojcik, Andrew; Achola, Edwin; Thoma, Colleen; Nixon, Cynthia; Tamura, Ronald (Inclusion, 2025)
Keywords: Extracurricular activity; Intellectual disability; Qualitative research; Semi-structured interview; dept.sed

Participation of students with intellectual and developmental disabilities in extracurricular activities: does inclusion end at 3:00? - Agran, Martin; Achola, Edwin; Nixon, Cynthia Allen; Wojcik, Andrew; Cain, Irma; Thoma, Colleen; Austin, Kira M.; Tamura, Ronald B. (Education and Training in Autism and Developmental Disabilities, 2017)
Although participation in extracurricular activities for students with intellectual and developmental disabilities has been advocated, a limited number of students appear to be involved in such activities. Further, there is little empirical research on how extracurricular activities are valued, supported, and encouraged. This study surveyed a sample of special educators across five states to learn about their opinions regarding extracurricular activities. As reported in other research, the findings confirm that few students participated in these activities; few parents requested these services for their children; and few teachers believed that planning them is their responsibility, despite the fact that they thought these activities were of value and provided several benefits. The implications of these findings are discussed.
Keywords: dept.sed